Experiences in La Colorada - Díaz Duque, R.O. (International Center for Tropical Agriculture, 1979)
An analysis is made of the sociocultural, technical and economic implications in the transfer of technology, based on experiences acquired with cassava farmers from the community of Media Luna, located on the Atlantic Coast of Colombia. It is concluded that the technician must assimilate the life style of the community in order to transmit the technology under the same conditions. Of the sociocultural aspects, the religious, political and folkloric ones are the most . important. New technology should be in line with traditional practices, which should be evaluated initially. All technology that represents an increase in income for the same cost will have immediate acceptance; thus a promising high- yielding var. should be introduced. Cultural practices should be demonstrated and taught in the form of suggestions. (CIAT)